Tuning of a Kagome Magnet: Insulating Ground State in Ga‐Substituted Cu4(OH)6Cl2. Issue 9 (20th February 2019) - Puphal, Pascal; Ranjith, Kizhake Malayil; Pustogow, Andrej; Müller, Max; Rogalev, Andrei; Kummer, Kurt; Orain, Jean‐Christophe; Baines, Christopher; Baenitz, Michael; Dressel, Martin; Kermarrec, Edwin; Bert, Fabrice; et al.
Abstract : Here, a successful synthesis method of the series Ga x Cu4– x (OD)6 Cl2 with substitutions up to x  = 0.8 is presented. The compound remains a frustrated kagome system with an insulating ground state similar to herbertsmithite for these substitutions, as the additional charge of Ga 3+ is most likely bound to additional OH − and Cl − . Besides infrared measurements, we present magnetic and specific‐heat data down to 2 K for selected samples with 0 ≤ x ≤ 0.8 . With increasing x the long‐range magnetic order is suppressed, similar to what is observed in the series Zn x Cu4 –x (OH)6 Cl2, indicating that Ga goes predominantly to the inter‐plane position of the layered crystal structure. The reduction of the frozen magnetic fraction with increasing substitution is followed by muon spin relaxation (μSR) measurements. 69, 71 Ga nuclear magnetic resonance (NMR) was applied as a local probe for Ga induced disorder. One well resolved Ga NMR line of moderate width is found for each isotope across the phase diagram which indicates a rather homogeneous distribution of the Ga isotopes on a single site in the lattice. Abstract : Ga x Cu4 –x (OD)6 Cl2 is successfully synthesized, but no Dirac metallic properties for 0 ≤ x ≤ 0.8 are found. In contrast, it is an insulating frustrated quantum spin system with magnetic properties similar to Zn x Cu4 –x (OD)6 Cl2 . Specific‐heat measurements show that the magnetically ordered fraction is continuously suppressed with increasing Ga substitution, consistently with muon spin relaxation and magnetization measurements.